2008
DOI: 10.1007/bf03173141
|View full text |Cite
|
Sign up to set email alerts
|

Some factors underlying mathematical performance: The role of visuospatial working memory and non-verbal intelligence

Abstract: Passive and active visuospatial working memory (VSWM) were investigated in relation to maths performance. The mental rotation task was employed as a measure of active VSWM whereas passive VSWM was investigated using a modified Corsi Blocks task and a matrix pattern task. The Raven Progressive Matrices Test measured fluid intelligenc e. A total of 128 students, aged 15-16, served as participants. Fluid intelligence and passive VSWM accounted for variance in overall maths performance. Active VSWM exhibited signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
146
3
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(186 citation statements)
references
References 77 publications
20
146
3
7
Order By: Relevance
“…A large longitudinal study of more than 70,000 children found that intelligence accounted for 59 % of the variance in mathematics scores (Deary, Strand, Smith, & Fernandes, 2007). Further empirical support for the importance of general intelligence, as measured by performance on Raven's Progressive Matrices (Raven, 1976), was provided by Kyttälä and Lehto (2008), who found that general intelligence predicted math achievement in a sample of ninth graders. Thus, intelligence seems to be important throughout the educational career of both younger and older children.…”
Section: Intelligence and Logical Reasoningmentioning
confidence: 99%
“…A large longitudinal study of more than 70,000 children found that intelligence accounted for 59 % of the variance in mathematics scores (Deary, Strand, Smith, & Fernandes, 2007). Further empirical support for the importance of general intelligence, as measured by performance on Raven's Progressive Matrices (Raven, 1976), was provided by Kyttälä and Lehto (2008), who found that general intelligence predicted math achievement in a sample of ninth graders. Thus, intelligence seems to be important throughout the educational career of both younger and older children.…”
Section: Intelligence and Logical Reasoningmentioning
confidence: 99%
“…Respecto al componente viso-espacial, en la línea de un estudio con adolescentes realizado por Kyttälä y Lehto (2008), parece que es únicamente la tarea que requiere una respuesta de tipo estático (relacionadas con la forma, el tamaño y la localización de los estí-mulos) la que aporta una contribución adicional, aunque menor, a la explicación de la ejecución matemática posterior.…”
Section: Conclusionesunclassified
“…Algunos estudios han investigado la posible influencia del tipo de tarea de MT viso-espacial en el desempeño matemático. Kyttälä y Lehto (2008) en una investigación con adolescentes encontraron que las tareas estáticas (centradas en la forma, el tamaño, el color o la localización de los estímulos) estarían más relacionadas con aprendizajes aritméticos y las dinámicas (movimiento, dirección o secuencia de estímulos) con geométricos.…”
Section: Introductionunclassified